Digestive Bleeding due to Vascular Malformations - Torterolo, Edgardo; Estapé, Gonzalo; Lizaso, Isabel; Ferrari, Ivonne; Ruocco, Alvaro; Carámbula, Julio C; Tiscornia, Eduardo; Goller, Wolfgang (Cirugía del Uruguay, 1980)
Sorne considerátions about . digestive vascular malformations are done. Two ca'ses of severe digestive bleeding due to ·angiodyspl'asia· of the small intestine . and colon are presented.